Subgrouping the users of a specialized app for eating disorders. Issue 4 (4th July 2018) - Sadeh-Sharvit, Shiri; Kim, Jane Paik; Darcy, Alison M.; Neri, Eric; Vierhile, Molly; Robinson, Athena; Tregarthen, Jenna; Lock, James D.
ABSTRACT: Although mobile technologies for eating disorders (EDs) are burgeoning, there is limited data about the clinical characteristics of individuals using specialized smartphone applications (apps) without accompanying traditional forms of treatment. This study evaluated whether the users of an ED app cluster in clinically meaningful groups. Participants were 1, 280 app users (91.3% female; mean age 27) who reported not being in a weekly treatment for their ED. A hierarchical cluster analysis distinguished five groups of participants, all approximating DSM-5 ED categories. One cluster comprised of non-female, ethnically diverse users with Bulimia Nervosa features. Findings suggest that app users resemble known patient classifications.